On the Importance of Equity in International Climate Policy: An Empirical Analysis - Andreas Lange; Carsten Vogt; Andreas Ziegler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
Based on unique data from a world-wide survey of agents involved in international climate policy, this paper empirically analyzes the importance of equity in this field. We find that equity issues are considered highly important in international climate negotiations and that the polluter-pays rule and the accompanying poor losers rule are the most widely accepted equity principles. Our econometric analysis shows a strong influence of the economic or emission performance of the agents? country on the importance of equity issues and principles: (i) Equity issues are seen as more important by individuals from G77/China countries or from countries with less current per capita GDP and less future per capita CO2 emissions. (ii) Agents from richer countries are less in favor of incorporating the polluter-pays and the ability-to-pay principle in future international climate agreements. (iii) The poor losers rule is more strongly supported by individuals from G77/China countries or by individuals from countries with less current per capita GDP. While these results are consistent with pure economic self-interest, the support for the egalitarian principle runs contrary to economic intuition: In the long-run, agents from richer countries are more in favor of incorporating the egalitarian principle. Furthermore, the effect of the economic performance variables on the desired degree of incorporating the polluter-pays principle interestingly becomes less significant in the long-run. This indicates that future international climate agreements could possibly be based on a combination of the polluter-pays, the egalitarian, and the poor losers rule.
Keywords: D63; Q54; Q48; H41; 330; International Climate Policy; International Environmental Negotiations; Equity Issues; Probit Models